(untitled) (Research, Society and Development, 2020)
This article presents the results of a research carried out with teachers of a public school in Ceará High School located in the metropolitan region of Fortaleza and aimed to discuss the concepts and perspectives of curriculum that guide the teaching activity of these teachers. Inserted in the qualitative research approach, this research used as a technique a questionnaire with open and closed questions, directed to 12 teachers, divided into 3 areas of knowledge: Languages and Codes and their technologies, Human Sciences and their technologies and Mathematics and their technologies, taking as theoretical reference the studies of Sacristan (2000), Saviane (2016) and Apple (2006). The central problem is the following question: “What is the concept of curriculum that guides the pedagogical practice of teachers?”. The results indicate that there are variations in the concept of school curriculum in the teachers’ view and that, in general, there is a concept of curriculum in the school referring only to the "grid" of subjects that the school has, that is, what is taught. to students daily.